2017
DOI: 10.3390/met7010021
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adsorption of Hydrogen on Al, Cu, Mg, Ti Surfaces in Al Alloy Melt via First Principles Calculation

Abstract: Adsorption of hydrogen on Al(111), Cu(111), Mg(0001), and Ti(0001) surfaces have been investigated by means of first principles calculation. The calculation of surface energy indicates that Mg(0001) is the most stable surface, while Ti(0001) is the most unstable surface among all the four calculated surfaces. The obtained adsorption energy shows that the interaction between Al and H atoms should be energetically unfavorable, and the adsorption of hydrogen on Mg(0001) surface was found to be energetically prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…for the three indexes, the value of zero indicates elastic isotropy while the variation from zero means anisotropic elastic properties. After calculation, it is found that the A U value of Ni (14) shear anisotropic factors A 2 and A 3 for the {010} and {001} planes are given as Equations (15) and (16), respectively,…”
Section: Elastic Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…for the three indexes, the value of zero indicates elastic isotropy while the variation from zero means anisotropic elastic properties. After calculation, it is found that the A U value of Ni (14) shear anisotropic factors A 2 and A 3 for the {010} and {001} planes are given as Equations (15) and (16), respectively,…”
Section: Elastic Anisotropymentioning
confidence: 99%
“…For example, the bulk modulus of L1 2 -ordered Ni 3 Al explored by Pearson et al is 229.2 GPa [8] while the value obtained by Yasuda et al is 171.0 GPa [9]. In order to break through the limitation derived from experimental methods, in recent years, first principles calculations have been successfully conducted to calculate the elastic properties of alloys and intermetallics [10][11][12][13][14]. Based on first principles, Wen et al [1] calculated the bulk modulus and Young's modulus of Ni 3 Al, as well as the effects of pressure on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The Al material performed better than Cu and SS throughout the operating condition which reflected both in the numerical and experimental results, which can be attributed to low mass transport losses. Yu et al [42] investigated an experiment on adsorption of Al, Cu, Mg, and Ti surfaces. Their results show that hydrogen adsorption on Al surfaces is more stable than other metals.…”
Section: Modeling Results Validationmentioning
confidence: 99%
“…Here, the lattice constant misfit ( ε ) is defined as the difference of lattice constant between substrate and film materials: ε = ( a substrate − a film )/ a substrate , where a is the lattice constant. The films with a low ε can keep a similar growth orientation of the substrate whereas the films with a large ε prefer to grow on the plane with a minimum surface energy, such as the (111) plane in fcc film, the (110) plane in bcc films, and the (011) plane in Ti and Co films with hcp structure . The simulated films grow in two main modes, namely the Volmer–Weber mode and the Frank–van der Merwe mode resulting from the different diffusion and mobility of various atoms.…”
Section: Resultsmentioning
confidence: 99%